Accounting as a Scientific Discipline within Economic Science - Wielgórska-Leszczyńska, Joanna (Studia Oeconomica Posnaniensia, 2014)
Accounting has great importance for economic science. Therefore, this article attempts to present accounting as a scientific discipline that has its own subject matter, purpose and methods of research, even though it is not considered to be a separate scientific discipline. A literature analysis has revealed a variety of opinions with regard to the characteristics of accounting as a theoretical and practical study. In addition it has been shown that accounting is closely related to finance, economics and management sciences, just as these disciplines are closely related to accounting. This is because accounting plays an important role in the field of economics, where the main area of concern is an entity (organization) and its relationship with its surroundings - this is the international language of business. Accounting is concerned with the analysis, principles of recording, valuation methods, and the evaluation of information concerning the activities of business organisations which have a financial dimension.